Analisis Lirik Lagu “Gala Bunga Matahari” Karya Sal Priadi Menggunakan Pendekatan Objektif - Zahwatul Laisya (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study aims to analyze the lyrics of the song Gala Bunga Matahari by Sal Priadi using an objective approach to reveal the structure, meaning, and semantic construction. Descriptive qualitative research methods with text analysis techniques are used to dissect the linguistic and stylistic components of the lyrics. The focus of the study includes aspects of language structure, use of diction, metaphors, and semantic patterns in the lyrics. The results of the study show that the lyrics of the song Gala Bunga Matahari have a high complexity of meaning with the use of rich natural metaphors. The structure of the lyrics displays a dichotomy between hope and reality, with sunflowers as the main symbol representing the dynamics of human life and feelings. The analysis found five main themes: longing, hope, emotional transition, uncertainty, and resilience. Linguistically, the lyrics use a metaphorical style of language with a high level of abstraction, presenting a complex relationship of meaning between natural objects and subjective experiences. Semantic construction shows the songwriter's ability to transform personal experiences into universal narratives. The conclusion of the study reveals that the lyrics of "Gala Bunga Matahari" are a symbolic representation of the human emotional journey, with sunflowers as a fundamental metaphor in expressing the dynamics of feelings and hopes.